Deciphering the Precursor–Performance Relationship of Single‐Atom Iron Oxygen Electroreduction Catalysts via Isomer Engineering. Issue 11 (20th January 2022) - Hong, Yaoshuai; Li, Longbin; Huang, Bingyu; Tang, Xiannong; Zhai, Weijuan; Hu, Ting; Yuan, Kai; Chen, Yiwang
Abstract: Single atom Fe–nitrogen–carbon (Fe–N–C) catalysts have high catalytic activity and selectivity for the oxygen reduction reaction (ORR), and are possible alternatives for Pt‐based materials. However, the reasonable design and selection of precursors to establish their relationship with Fe–N–C catalyst performance is still a formidable task. Herein, precursors with controllable structures are easily achieved through isomer engineering, with the purpose of regulating the active site density and microscopic morphology of the final electrocatalyst. As‐proof‐of‐concept, phenylenediamine isomers‐based polymers are used as precursors to fabricate Fe–N–C catalysts. The Fe–P p PD‐ 800 derived from p ‐phenylenediamine shows that the best ORR activity with a half‐wave potential ( E 1/2 ) reaches 0.892 V vs reversible hydrogen electrode (RHE), which is better than the counterparts derived from o ‐phenylenediamine (Fe–P o PD‐ 800 ) and m ‐phenylenediamine (Fe–P m PD‐ 800 ), even surpassing commercial Pt/C ( E 1/2 = 0.881 V vs RHE). Furthermore, the self‐made zinc–air battery based on Fe–P p PD‐ 800 achieves high power density and specific capacity up to 242 mW cm −2 and 873 mA h gZn −1 respectively, a stable open circuit voltage of 1.45 V, and excellent cycling stability. This work not only proves the practicability of adjusting the catalytic activity of single‐atom catalysts through isomer engineering, but also provides an approach to understand the relationship between precursors and target catalysts performance. Abstract : The control of different nitrogen/carbon precursors is achieved through isomer engineering with the purpose of regulating active site density and microscopic morphology of Fe–N–C catalyst, which provides a strategy for understanding the relationship between precursors and corresponding catalyst performance toward rational design and fabrication of efficient oxygen reduction reaction catalysts.